Eksistensi Perempuan Dalam Kumpulan Cerpen Bulan Di Atas Lovina Karya Yvonne De Fretes - Kadek Sintya Purnama Dewi; Jalu Norva Illa Putra (Jurnal Pengetahuan dan Pendidikan, 2025)
This research aims to determine the existence of women in a collection of short stories. The theory used in this study is existentialist feminism. The method used in this study is a literature study method with data source sampling techniques, notes, and writing. Furthermore, to analyze the data using a descriptive method with data collection and data analysis techniques. The results of the analysis are presented using a descriptive method. Based on the analysis, the results of the study were found in the short story collection Bulan di Atas Lovina by Yvonne De Fretes, namely as follows. First, working women who are in love and free women. Second, the messages contained in the short stories include implied messages and explicit messages.